Optimization of the Photo-Fenton process for the effective removal of chemical oxygen demand and phenols in portable toilet wastewater: A treatment study under real world conditions - Yorgi San juan-Garisado; Francisco Luna-Guevara; Pablo Alberto Herrera; Jonathan Soto-Paz; Jesus David Alvarez-Trujillo; Cristian Mejia-Parada; Brayan Alexis Parra-Orobio (Heliyon, 2024)
Wastewater from portable toilets (WWPT) is characterized by a high content of organic matter and a variety of chemical compounds that retain bad odors, especially phenols, a type of pollutant that is difficult to degrade by conventional treatments; in addition, it is persistent, toxic, and accumulates in the aquatic environment. Although different successful experiences with the use of Photo-Fenton are reported in the scientific domain, its application in WWPT is scarce and warrants study due to the wide use of portable toilets. The objective of this study was to evaluate the Photo-Fenton oxidation process in the removal of organic matter expressed as COD in a WWPT, as well as the reduction of phenols and BOD5. The experimental runs were carried out in a 0.50 L batch reactor to evaluate the effect of the factors (H2O2: 0.019, 25.56, 40.67, 87.24, 148.91, 174.45 g L−1 and pH: 2.80, 3.00, 3.27, 4.40, 5.53, 6.00 UNT) on COD removal and sludge production. It was found that the optimum operating conditions of pH 4.72 and H2O2 dosage of 174.45 g L−1 reduced the concentration of phenols by 97.83 % and 95.49 % of COD. In addition, 98.01 % of BOD5 was reduced, resulting in a biodegradability ratio (BOD5/COD) of 0.23 compared to the untreated wastewater of 0.53. From a cost perspective, the use of Photo-Fenton to treat wastewater under these conditions would be US$ 1.15 per liter.